Draft Genome Sequence of Mycobacterium houstonense Strain ATCC 49403(T) - Levasseur, Anthony (Genome Announc, 2016)
Mycobacterium houstonense is a nontuberculous species rarely responsible for human infection. The draft genome of M. houstonense ATCC 49403(T) comprises 6,451,020 bp, exhibiting a 66.96% G+C content, 5,881 protein-coding genes, and 65 predicted RNA genes.